Pulmonary Delivery of Virosome-Bound Antigen Enhances Antigen-Specific CD4+ T Cell Proliferation Compared to Liposome-Bound or Soluble Antigen - Blom, Rebecca A. M.; Amacker, Mario; van Dijk, R. Maarten; Moser, Christian; Stumbles, Philip A.; Blank, Fabian; von Garnier, Christophe (Frontiers in Immunology, 2017)
Pulmonary administration of bio-mimetic nanoparticles loaded with antigen may represent an effective strategy to directly modulate adaptive immune responses in the respiratory tract. Depending on the design, virosomes may not only serve as bio-mimetic antigen carriers, but are also endowed with intrinsic immune-stimulatory properties. We designed fluorescently labeled influenza-derived virosomes and liposome controls coupled to the model antigen ovalbumin to investigate uptake, phenotype changes and antigen processing by antigen-presenting cells exposed to these particles in different respiratory tract compartments. Both virosomes and liposomes were captured by pulmonary macrophages and dendritic cells alike and induced activation in particle bearing cells only by up-regulation of co-stimulatory markers such as CD40, CD80, CD86, PD-L1, PD-L2 and ICOS-L. Though antigen processing and accumulation of both coupled and soluble antigen was similar between virosomes and liposomes, only ovalbumin-coupled virosomes generated a strong antigen-specific CD4+ T cell proliferation. Pulmonary administrated antigen-coupled virosomes therefore effectively induced adaptive immune responses and may be utilized in novel preventive or therapeutic approaches in the respiratory tract.